Intégrales

Règles d'intégration
Fonction f (x) ò f(x) dx'
ò xn dx = (1 / (n+1)) . x n+1 + C , si n ¹ -1
ò dx / x = ln x + C
ò [ u (x) ± v (x)] dx = ò u (x) dx ± ò v (x) dx
ò [u' (x) / u (x)] dx = ln u (x) + C
ò u (x) . u' (x) dx = (1 / 2) . u (x)2 + C

Intégration par parties
Fonction f (x) ò f(x) dx'
ò u (x) . v' (x) dx = u (x) . v (x) - ò u' (x) . v (x) dx

Méthode de substitution
Fonction f (x) ò f(x) dx'
ò f (x) dx =

Intégration (sans la constante d'intégration C)
Fonction f (x) ò f(x) dx'
   
   
   
   
   
 
   
   
   
   
   
 

 

 

Intégrale =

 e-mail